2007
DOI: 10.1038/sj.bjc.6603645
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of capecitabine and irinotecan in combination with concurrent pelvic radiotherapy (CapIri-RT) as neoadjuvant treatment of locally advanced rectal cancer

Abstract: We sought to evaluate the efficacy and safety data of a combination regimen using weekly irinotecan in combination with capecitabine and concurrent radiotherapy (CapIri-RT) as neoadjuvant treatment in rectal cancer in a phase-II trial. Patients with rectal cancer clinical stages T3/4 Nx or N þ were recruited to receive irinotecan (50 mg m À2 weekly) and capecitabine (500 mg m À2 bid days 1 -38) with a concurrent RT dose of 50.4 Gy. Surgery was scheduled 4 -6 weeks after the completion of chemoradiation. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 26 publications
3
62
1
2
Order By: Relevance
“…However, the rate of grade III/IV toxicity (10%) noted in this study is comparable with that reported for oxaliplatin regimes (18 -30%) (Alonso et al, 2004(Alonso et al, , 2007Casado et al, 2004;Tucci et al, 2004;Fakih et al, 2005;Machiels et al, 2005;Avallone et al, 2006;Rutten et al, 2006;Rödel et al, 2007). Indeed, the findings of this study suggest a safety profile for irinotecan, 5-FU and radiotherapy that is comparable with previously reported findings with capecitabine and radiotherapy (rate of grade III/IV diarrhoea 12 -28%) (Mehta et al, 2003;Navarro et al, 2003;Mitchell et al, 2004;Mohiuddin et al, 2006;Willeke et al, 2007), but using a lower radiation dose (45 Gy as opposed to 50.4 Gy in the capecitabine regimen).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the rate of grade III/IV toxicity (10%) noted in this study is comparable with that reported for oxaliplatin regimes (18 -30%) (Alonso et al, 2004(Alonso et al, , 2007Casado et al, 2004;Tucci et al, 2004;Fakih et al, 2005;Machiels et al, 2005;Avallone et al, 2006;Rutten et al, 2006;Rödel et al, 2007). Indeed, the findings of this study suggest a safety profile for irinotecan, 5-FU and radiotherapy that is comparable with previously reported findings with capecitabine and radiotherapy (rate of grade III/IV diarrhoea 12 -28%) (Mehta et al, 2003;Navarro et al, 2003;Mitchell et al, 2004;Mohiuddin et al, 2006;Willeke et al, 2007), but using a lower radiation dose (45 Gy as opposed to 50.4 Gy in the capecitabine regimen).…”
Section: Discussionsupporting
confidence: 82%
“…Six small studies are published as full papers (Kalofonos et al, 2003;Mehta et al, 2003;Klautke et al, 2005;Mohiuddin et al, 2006;GlynneJones et al, 2007;Willeke et al, 2007). To conclude, the combined RCT regimen irinotecan plus 5-FU with radiation therapy appears to be a tolerable adjuvant therapy (Kalofonos et al, 2003) that results in a good tumour response when given pre-operatively to patients with rectal cancer in whom resection is either possible or uncertain (Mehta et al, 2003;Klautke et al, 2005).…”
mentioning
confidence: 99%
“…21 The addition of a second chemotherapeutic agent to neoadjuvant capecitabine-based CRT with cetuximab has not demonstrated a marked improvement to the rates of pCR or tumor downstaging in LARC, 24 which remain similar to those reported from studies of neoadjuvant capecitabine-based CRT, 12,13,25 or capecitabine-based CRT with irinotecan or oxaliplatin. 26,27 In the present study an assessment of radiological tumor response according to RECIST criteria was made. An overall response rate of 71% was recorded, which was similar to the that reported for patients with locally advanced SCCHN receiving cetuximab in combination with radiotherapy.…”
Section: Neoadjuvant Cetuximab Plus Crt On Tumor Response In Larcmentioning
confidence: 99%
“…• Irinotecan: Phase II trials have found a dose-dependent improved pCR rates (0-24%) with irinotecan implemented in CRT with acceptable toxicity (184,185), and a German study found pCR of 15% (186). A recent phase III trial reported no improved efficacy and increased toxicity of irinotecan when implemented in postoperative CRT after a 3-year follow-up (187).…”
Section: New Crt Regimensmentioning
confidence: 99%